2022
DOI: 10.3390/microorganisms10102016
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Circulation of Usutu and West Nile Viruses: A One Health Approach in Humans, Domestic Animals and Mosquitoes in Burkina Faso, West Africa

Abstract: Usutu virus (USUV) and West Nile virus (WNV) are phylogenetically closely related arboviruses. These viruses mainly follow an enzootic cycle involving mosquitoes and birds, but they occasionally infect humans and other mammals, inducing neurotropic disorders. Since the discovery of USUV, only two human cases have been reported in Africa, including one in Burkina Faso in 2004. Since then, no studies have been conducted to measure the extent of the circulation of this virus in Burkina Faso, and no study regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…SINV detection was validated through virus isolation and PCR from non-blood-engorged females. Previously, a PCR-based survey on the same samples did not detect six mosquito-borne viruses potentially present in the country (dengue virus, Zika virus, chikungunya virus, West Nile virus and Usutu virus) [20,21], just like found here in the metagenomics survey. Comparison of the surveys using either PCR or metagenomics suggests that viral metagenomics on mosquitoes is a suitable tool for virus surveillance in regions with a high viral diversity, as shown by others [46,47].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…SINV detection was validated through virus isolation and PCR from non-blood-engorged females. Previously, a PCR-based survey on the same samples did not detect six mosquito-borne viruses potentially present in the country (dengue virus, Zika virus, chikungunya virus, West Nile virus and Usutu virus) [20,21], just like found here in the metagenomics survey. Comparison of the surveys using either PCR or metagenomics suggests that viral metagenomics on mosquitoes is a suitable tool for virus surveillance in regions with a high viral diversity, as shown by others [46,47].…”
Section: Discussionsupporting
confidence: 68%
“…This West-African country is highly connected to other regions in Africa and other continents through human and wildlife movement [19]. Several mosquito-borne viruses have been previously detected in Burkina Faso [20][21][22]. Nevertheless, studies have focused on a limited number of these viruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fever and skin rash were reported for both cases. Since, all human cases of USUV infection have been reported in Europe only, although seroprevalence studies conducted in other countries highlight the active circulation of this virus in the African continent [ 50 , 51 ] ( Table 1 ).…”
Section: Human Infectionsmentioning
confidence: 99%
“…Subsequent human cases have emerged primarily in Europe. Despite evidence of active virus circulation in Africa from seroprevalence studies no further human disease cases have been reported there [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%